Diatomaceous Soils and Advances in Geotechnical Engineering—Part II - Daniel Zuluaga-Astudillo; Carlos Slebi-Acevedo; Juan Carlos Ruge; Javier Camacho-Tauta; Bernardo Caicedo-Hormaza (Buildings, 2023)
In the geotechnical area, advances in diatomaceous soil research are laconic and mainly oriented towards understanding the primary soil response (typical characterization methods) considering observation and experience (failures in construction processes or unexpected laboratory results) more than following a scientific method. Coincident results have been evidenced in the correspondence between the content of frustules, the effective friction angle and the water retention capacity. However, the variables and processes that control some mechanical behaviors have yet to be documented in the literature, such as the level of fracturing of the frustules and its relation with interlocked behavior, compressibility and shear strength. In addition to the bibliographic background, SEM microscopy records are presented. These facilitate the understanding of the described phenomena. The images highlight the level of deterioration, the environment, the morphology and the pores present in diatoms of different origins. The morphology (as a function of the species) of intact or fractured frustules (depending on the stress record) affects the mechanical responses and volumetric variations of the diatomaceous deposits. Furthermore, this review presents some emerging research lines in diatomaceous soils, such as the subjection of structures to geotechnical centrifuge conditions, some constitutive models and the criteria for developing water retention curves.